Has the liberal internationalist conception of the EU’s foreign policy made it incapable of acting in international conflicts? - Durnik, Mitja (Teorija in praksa, 2023)
Notions of the power associated with the European Union’s foreign policy and its role in international relations are mostly liberal in origin. This explains the EU’s special role in the Cold War era and that it has since emerged more as a moral, ethical and normative power. The EU’s lack of military capability has probably been the main cause that prevents it from acting as a great or superpower. The distinction between materialistic and immaterial elements of power has been a crucial point of contention between realists and liberal thinkers. In international relations, we are also witnessing the trend of the EU increasingly using the geopolitical approach (such as in the Ukrainian crisis) besides the normative one. In the article, different concepts of EU foreign policy regarding power in the light of realism and liberalism are compared where, alongside the descriptive method, a SWOT analysis is performed.
Keywords: Evropska unija; liberal internationalist concept; liberalini internacionalizem; Liberalizem; mednarodni konflikti; Mednarodni odnosi; Obvladovanje konfliktov; political power; political realism; politična moč; politični koncepti; realism; realizem; rusko-ukrajinski konflikt; zunanja politika; Zunanji odnosi